Application of compost amended with biochar on the distribution of antibiotic resistance genes in a soil–cucumber system—from the perspective of high-dose fertilization - Shi, Shuai; Tong, Zhenye; Sun, Bo; Wei, Yiyang; Tian, Yu; Zuo, Qihui; Qiao, Xingxing; Duan, Jiaze; Bi, Wenlong; Qin, Junmei; Zhou, Jun; Liu, Fenwu (Frontiers in Microbiology, 2025)
The transfer of antibiotic resistance genes (ARGs) from soils to vegetables negatively impacts human health. This study explored the effects of the high-dose (18.73 t/ha) application of traditional compost (TC) and composts produced through the co-composting of traditional materials with large-sized (5–10 mm) biochar-amended compost (LBTC) or small-sized (< 0.074 mm) biochar-amended compost (SBTC) on the distribution of ARGs in a soil–cucumber system were explored. Results indicated that the SBTC group had the highest soil nitrogen, phosphorus, and potassium contents, followed by the LBTC, TC, and control treatment groups. These findings aligned with the quality and weight of harvested cucumbers. Bacterial community diversity decreased in compost-fertilized soils. Compared with their preexperimental values in soils, the total absolute abundances of ARGs and mobile genetic elements (MGEs) increased by 23.88 and 6.66 times, respectively, in the control treatment group; by 5.59 and 5.23 times, respectively, in the TC group; by 5.50 and 1.81 times, respectively, in the LBTC group; and by 5.49 and 0.47 times, respectively, in the SBTC group. Compared with those in the control treatment group, the absolute abundance of ermB, ermT, gyrA, qnrS, tetC, and intI1 decreased by 6–100% in the soil of the SBTC group. Compost application to soils significantly decreased ARG abundance in cucumbers; SBTC had the most significant effect and reduced the number of host bacteria at the phylum level from four to three. Nutrient levels in soils were important factors influencing the migration of ARGs from soils to cucumbers. In summary, when compared to other composts, the high-dose (18.73 t/ha) application of SBTC is more effective at reducing the risk of the accumulation and transfer of ARGs in the soil–cucumber system.